Ambiguity and Symbolism in the Implementation of the ECOWAS Free Movement Protocol: Evidence from Ghana and Sierra Leone (African Human Mobility Review, 2021)
This paper examines the challenges to the implementation of the EconomicCommunity of West African States (ECOWAS) Protocol on Free Movement, withparticular reference to Ghana and Sierra Leone. The paper is based on a desktopreview and in-depth interviews with selected ECOWAS migrants and officials ofinstitutions responsible for managing migration in Ghana and Sierra Leone. Thefindings suggest that Ghana and Sierra Leone have made modest progress in theimplementation of the protocol. Apart from abolishing visa and entryrequirements for 90 days, both countries have adopted the standardizedECOWAS Travel Certificate. Despite a few achievements, the following challengesaffect the implementation of the free movement protocol in both countries:Policy ambiguities resulting from contradictions between national laws onemployment and the ECOWAS Free Movement Protocol; harassment of migrants;migrants’ lack of travel documents; low level of knowledge about the ECOWASprotocol; resource constraints; fears of competition with immigrants, especiallyin Ghana; securitization of migration and migrants; weak labour market andmigration information systems, economic challenges and political instability.This paper concludes that the future implementation outcomes of the ECOWASprotocol largely depend on the commitment of the member states and financialsupport that they receive from ECOWAS and its development partners.